Brain health INnovation Diplomacy: a model binding diverse disciplines to manage the promise and perils of technological innovation. (13th August 2020) - Ternes, Kylie; Iyengar, Vijeth; Lavretsky, Helen; Dawson, Walter D.; Booi, Laura; Ibanez, Agustin; Vahia, Ipsit; Reynolds, Charles; DeKosky, Steven; Cummings, Jeffrey; Miller, Bruce; Perissinotto, Carla; et al.
ABSTRACT: Background: Brain health diplomacy aims to influence the global policy environment for brain health (i.e. dementia, depression, and other mind/brain disorders) and bridges the disciplines of global brain health, international affairs, management, law, and economics. Determinants of brain health include educational attainment, diet, access to health care, physical activity, social support, and environmental exposures, as well as chronic brain disorders and treatment. Global challenges associated with these determinants include large-scale conflicts and consequent mass migration, chemical contaminants, air quality, socioeconomic status, climate change, and global population aging. Given the rapidly advancing technological innovations impacting brain health, it is paramount to optimize the benefits and mitigate the drawbacks of such technologies. Objective: We propose a working model of Brain health INnovation Diplomacy (BIND). Methods: We prepared a selective review using literature searches of studies pertaining to brain health technological innovation and diplomacy. Results: BIND aims to improve global brain health outcomes by leveraging technological innovation, entrepreneurship, and innovation diplomacy. It acknowledges the key role that technology, entrepreneurship, and digitization play and will increasingly play in the future of brain health for individuals and societies alike. It strengthens the positive role of novel solutions, recognizes and works to manage both real and potential risks of digital platforms. It is recognition of the political, ethical, cultural, and economic influences that brain health technological innovation and entrepreneurship can have. Conclusions: By creating a framework for BIND, we can use this to ensure a systematic model for the use of technology to optimize brain health.